High vaccine confidence and strong approval of the mandatory immunization schedule among Bulgarian general practitioners in 2022 - Veronika Dimitrova; Savina Stoitsova; Vanya Rangelova; Ralitsa Raycheva; Maria Martinova; Gergana Nenova; Milena Iakimova; Irina Georgieva; Ivo Georgiev; Stefka Krumova; Antoaneta Minkova; Nadezhda Vladimirova; et al. (Human Vaccines & Immunotherapeutics, 2023)
In a context of recently decreasing childhood immunization coverage and low uptake of COVID-19 vaccines in Bulgaria, this study measures vaccine hesitancy among general practitioners (GPs) in the country, as they are central to forming patients’ attitudes. In 2022, a face-to-face survey was conducted through a simple random sample from an exhaustive national database of Bulgarian GPs. This study measured attitudes on vaccine importance, safety, and effectiveness, and attitudes toward the Bulgarian immunization schedule. Information was collected on demographic and GP practice characteristics and possible predictors of vaccine confidence in order to test for associations with attitudes toward immunization. GP attitudes toward vaccines and the immunization schedule in Bulgaria were generally positive. Among 358 respondents, 351 (98%,95%CI96–99%) strongly agreed/agreed that vaccines are important, 352 (98%,95%CI96–99%) that vaccines are effective, and 341 (95%,95%CI93–97%) that vaccines are safe. 347 respondents (97%,95%CI95–98%) affirmed that “it’s good that vaccines from the children’s immunization schedule are mandatory”, and 331 (92%,95%CI89–95%) agreed with the statement “Bulgaria’s childhood immunization has my approval”. Trust in information from official institutions was among the strongest predictors of vaccine confidence. Respondents’ vaccine confidence levels are within the ranges reported by GPs in other European countries and above those reported within the general Bulgarian population. GPs’ vaccine confidence is highly associated with trust in official institutions. It is important to maintain trust in official institutions and to support GPs in communicating vaccine knowledge with patients so that vaccine hesitancy in the general population is countered.